2014
DOI: 10.1111/jfpe.12085
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Functional Properties of Water‐Soluble Dietary Fiber from Apple Pomace

Abstract: The extraction of water‐soluble dietary fiber (SDF) from apple pomace (AP) by cellulase, microwave‐ and ultrasound‐assisted methods was studied in comparison with conventional acid method. The functional properties of extracted SDFs were further evaluated, and the speciality of each method was clarified in order to suggest the right method to adopt for practice. Results indicated that AP is rich in SDF, which is significantly potential to be applied in food processing. Acid hydrolysis of AP gave 10.3% of SDF, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 22 publications
0
26
0
1
Order By: Relevance
“…Yan and Kerr () observed that TDF ranged from 442 to 495 g/kg in vacuum‐dried pomace and was not significantly different from the freeze‐dried pomace (480 g/kg). Ultrasound‐assisted extraction provided higher soluble dietary fiber yield in apple pomace than when microwave or acid hydrolysis techniques were used (Li and others ).…”
Section: Bioactive Compounds From Fruit and Vegetable Losses And Wastementioning
confidence: 99%
“…Yan and Kerr () observed that TDF ranged from 442 to 495 g/kg in vacuum‐dried pomace and was not significantly different from the freeze‐dried pomace (480 g/kg). Ultrasound‐assisted extraction provided higher soluble dietary fiber yield in apple pomace than when microwave or acid hydrolysis techniques were used (Li and others ).…”
Section: Bioactive Compounds From Fruit and Vegetable Losses And Wastementioning
confidence: 99%
“…Similar findings were reported by other studies (Ying et al , ; Bélafi‐Bakó et al , ; Sommano et al , ). Li et al () studied MAE for SDF from apple pomace. The SDF yield by MAE (14.9%) was higher than by conventional method (10.3%) with drastic efficiency, as the conventional method was conducted for 4 h, while MAE was operated only 2 min.…”
Section: Resultsmentioning
confidence: 99%
“…The major sources for commercial pectin production are apple pomace, citrus peels, and sugar beet pulp (Mesbahi, Jamalian, & Farahnaky, ). Apple pomace is the solid residue produced in a large quantity during apple juice extraction in the industry (Li, He, Lv, & He, ). More than 100 million tons of this by‐product resource is produced in China every year (Cheng, Sun, Du, & Jian, ).…”
Section: Introductionmentioning
confidence: 99%